Perceptual acuity ability applied for endurance runners: The validity of a just noticeable difference approach - Krause, M. P.; Antonio, D. S.; Haile, L.; de Macedo Salgueirosa, C.; Robertson, R. J. (Perceptual and Motor Skills, 2025)
Endurance runners need to self-regulate their pace continuously in a race so that the ideal performance can be sustained without fatigue. Hence, we are interested in validating an approach to measure individual perceptual acuity ability using just noticeable differences (JND) in a physical stimulus, and its related psychophysiological demands. Fifteen male runners (M age = 34.27, SD = 6.91 years) first performed a maximal treadmill test to determine the speed of a standard exercise bout for the JND trials. The JND trials consisted of four 5-min running bouts on a treadmill with 5-min rest between bouts. For bouts 1 and 3, participants ran at the standard stimulus (SS) pace, but for bouts 2 and 4, they adjusted their speeds to achieve a level of exertion at a JND above/below the SS. They achieved differences in the final 30 seconds of the VO2 between each JND bout and the previous SS at just above (JND-A) and just below (JND-B) the JND perceived exertions. We assessed the JND approach validity by intraclass correlation coefficient (ICC), coefficient of variation (CoV), concordance correlation coefficient (CCC), Bland-Altman and Cohen`s d for VO2 of two standard stimuli within each JND trial. All validity statistical tests indicated a high level of concordance and agreement within both JND at 70%VO2max and 80%VO2max (ICC = .896 and .940; CoV 2.77 and 2.05; CCC = .889 and .936; respectively); with low standard error of measurement and of the estimate (1.261 and 1.0105; 1.6932 and 1.3868; respectively) (all p = .05). The data also showed a high level of agreement since the measures are within 95% limits in each JND trial. Our findings established the validity and reproducibly of the JND approach to identify the perceptual acuity ability applied to endurance male runners.